Collectivisation in Lithuania 1947–1952: Decisions and Control by the CC of the All-Union CP - Pocius, Mindaugas (Genocidas ir rezistencija, 2019)
The profound Soviet economic, social and cultural transformation of the rural life was supposed to take place in agrarian Lithuania as well, but in the first post-war years it was postponed for some time because of the strong anti-Soviet armed resistance and the weakness of the communist government in the province. By the beginning of 1949, the guerrilla movement had already weakened considerably, the authorities in the rural areas had become stronger, the radical land reform of 1944–1948 had been completed, and in 1948 the buožės (wealthy farmers) were exiled from the villages. The conditions were favourable for the big break, i.e. the general forced collectivisation.
Keywords: Lithuania; Soviet occupation; communist party; collectivisation